Proposta de intervenção para sensibilização dos gestores municipais quanto à implementação do serviço de acupuntura na saúde mental do municípo Castanhal, Pará - SILVA, Jessé Jerônimo Fernandes e (Universidade Federal do Pará, 2023)
Introduction: Depression encompasses biopsychosocial imbalances and is potentiated by stressful events. The progression of this, restricting quality of life through the exacerbation of negative symptoms and escape and avoidance behavior. Among the treatment approaches, acupuncture has proven effective for therapeutic success Objective: Application of the acupuncture technique in patients with depression disorder as an intervention proposal to sensitize municipal managers regarding the implementation of the mental health service in the municipality of Castanhal, Pará. Method: This was a quasi-experimental study with a quanti-qualitative approach, without a control group, with 17 participants. The data collection used a sociodemographic questionnaire, acupuncture form, Hamilton Scale, SF-12 Quality of Life questionnaire and field diary, the latter categorized into three domains, "quality of sleep", "quality of life" and "anxiety". Nine sessions were performed with a maximum use of 20 needles in each session. The data obtained were analyzed by descriptive statistics with the aid of SPSS software, using the chi-square test and the Student's t-test. Results: The majority of participants were female, in the age range 31 to 40 years, married, high school education, no fixed income, practice evangelism, perform household labor activities, have no children, smoker, sedentary, with unstable relationship in childhood and sexual abuse. The results showed improvement in the signs and symptoms associated with depression with a reduction in the Hamilton score from 19.3 ± 3.77 to 13.13 ± 2.43, student's t=5.6830, p=0.001, besides the improvement in the perception of general health status from the SF-12 from 4.06 ± 1.09 to 1.86 ± 0.83, p=0.001. Conclusion: The intervention with systemic acupuncture showed effective results in patients with depression, besides reducing complaints of anxiety crisis, improvement in sleep quality and concentration of the participants.